Pengaruh Variasi Konfigurasi Cerucuk Bambu terhadap Nilai Kuat Tekan Bebas Tanah Lempung - Catur Bejo Santoso; Ahmad Utanaka; Dora Melati Nurita Sandi; Megalita Rodiyani (LPPM Universitas Mataram, 2026)
High-plasticity clay soil commonly exhibits low bearing capacity and therefore requires an effective, economical, and applicable reinforcement method. This study aims to analyze the effect of bamboo pile length variation on the unconfined compressive strength of clay soil from Kedungdandang Hamlet, Tapanrejo Village, Muncar District, Banyuwangi Regency. Disturbed soil samples were collected at a depth of 70 cm and characterized through sieve analysis, water content, specific gravity, unit weight, and Atterberg limit tests. Mechanical performance was evaluated using the Unconfined Compression Test on untreated clay and clay reinforced with bamboo piles measuring 3 mm in diameter, 1.25 cm spacing, and lengths of 3.5, 5, and 7.5 cm. The soil was classified as high-plasticity clay, with a liquid limit of 81.81% and plasticity index of 46.96%. The average UCS increased from 26.60 kPa to 32.66, 36.61, and 47.19 kPa. The 7.5 cm piles provided the highest improvement, 77.41% over untreated soil.